Current Experience of Ultrasound Training in Otolaryngology Residency Programs. (12th August 2018) - Meister, Kara D.; Vila, Peter M.; Bonilla‐Velez, Juliana; Sebelik, Merry; Orloff, Lisa A.
Abstract : Objectives: The applications of using ultrasound for the evaluation and management of otolaryngologic diagnoses are expanding. The purpose of this study was to evaluate the current experience of ultrasound training in otolaryngology residency programs. Methods: All allopathic and osteopathic otolaryngology residency programs in the United States were surveyed online via an e‐mailed survey link to the resident representatives of the Section for Residents and Fellows in Training of the American Academy of Otolaryngology–Head and Neck Surgery. We present a descriptive analysis of the survey results. Results: A total of 110 responses were obtained from resident representatives at MD and DO otolaryngology residency programs, representing a response rate of 94.8%. Forty‐four percent of residents reported that they would not feel comfortable with performing ultrasound‐guided procedures after residency; 43% reported that they do not perform ultrasound procedures as a part of their residency training; and 60% of those trainees performing ultrasound procedures do not log the procedures. Twenty‐three percent of residents did not have access to an ultrasound machine. Most respondents (71%) desired more exposure to diagnostic and/or interventional ultrasound training during residency. Conclusions: Although current experience is variable, there is a strong interest in increasing resident skill acquisition in ultrasound training among otolaryngology residents. Some barriers to these goals may be a lack of trained faculty members using ultrasound and insufficient recording mechanisms for residents performing ultrasound procedures.